2006
DOI: 10.1242/dev.02318
|View full text |Cite
|
Sign up to set email alerts
|

DrosophilaIk2, a member of the IκB kinase family, is required for mRNA localization during oogenesis

Abstract: In both Drosophila and mammals, IB kinases (IKKs) regulate the activity of Rel/NF-B transcription factors by targeting their inhibitory partner proteins, IBs, for degradation. We identified mutations in ik2, the gene that encodes one of two Drosophila IKKs, and found that the gene is essential for viability. During oogenesis, ik2 is required in an NF-B-independent process that is essential for the localization of oskar and gurken mRNAs; as a result, females that lack ik2 in the germline produce embryos that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 81 publications
3
64
0
Order By: Relevance
“…Although the requirement of Ik2 signaling in dendrite severing may involve DIAP1 downregulation, inactivation of Ik2 function caused a much stronger dendrite severing phenotype than DIAP1 GOF mutation did, suggesting that Ik2 signals might be mediated by pathways other than or in addition to those involving DIAP1 and caspases to trigger dendrite severing in class IV da neurons during dendrite pruning. The function of ik2 is also required in several other developmental processes in Drosophila, including the regulation of F actin dynamics during trachea and bristle morphogenesis, and the organization of cytoskeletons for proper mRNA localization during oogenesis (18,19,21). One common feature in all these developmental processes is the dynamic organization of cytoskeletons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the requirement of Ik2 signaling in dendrite severing may involve DIAP1 downregulation, inactivation of Ik2 function caused a much stronger dendrite severing phenotype than DIAP1 GOF mutation did, suggesting that Ik2 signals might be mediated by pathways other than or in addition to those involving DIAP1 and caspases to trigger dendrite severing in class IV da neurons during dendrite pruning. The function of ik2 is also required in several other developmental processes in Drosophila, including the regulation of F actin dynamics during trachea and bristle morphogenesis, and the organization of cytoskeletons for proper mRNA localization during oogenesis (18,19,21). One common feature in all these developmental processes is the dynamic organization of cytoskeletons.…”
Section: Discussionmentioning
confidence: 99%
“…2C, D, and G). Third, 2 independent ik2 EMS mutant alleles, ik2 1 and ik2 alice (21), were used in MARCM analyses to examine the role of ik2 during neuronal development in larvae and during dendrite severing in pupae. In larvae, the dendritic morphology of all 4 classes da neurons in ik2 mutant MARCM clones was indistinguishable from that in the wild-type clones.…”
Section: Sequence Of Events In the Dendrite Pruning Of Drosophila Senmentioning
confidence: 99%
See 1 more Smart Citation
“…This was as a result of misannotation in their laboratory stock list. Both alleles are strong loss-of-function alleles with a missense mutation in the kinase domain and show similar phenotypes (Oshima et al, 2006;Shapiro and Anderson, 2006). Therefore, this error does not affect the conclusions of the paper.…”
mentioning
confidence: 94%
“…Previously, we and others have shown that mutations in spindle-F (spn-F) and in the Drosophila IKK homologue ik2, affect both egg chamber polarity and bristle development (Abdu et al, 2006;Shapiro and Anderson, 2006). It has been demonstrated that the defects in egg chamber development in spn-F and ik2 are attributed to their effect on mRNA localization by regulating oocyte cytoskeleton organization.…”
Section: Introductionmentioning
confidence: 99%